1999
DOI: 10.1161/01.hyp.34.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Brain Renin-Angiotensin System and Ouabain-Induced Sympathetic Hyperactivity and Hypertension in Wistar Rats

Abstract: Abstract-In Dahl salt-sensitive rats on a high salt diet or normotensive rats with chronic central infusion of sodium, increased brain "ouabain" results in sympathetic hyperactivity and hypertension, possibly by activating the brain renin-angiotensin system. In the present study, we tested whether the hypertension caused by exogenous ouabain also depends on activation of brain renin-angiotensin system. In Wistar rats, ouabain (50 g/d) was infused subcutaneously for 14 days with the use of osmotic minipumps. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 30 publications
4
70
0
4
Order By: Relevance
“…As previously demonstrated, long-term treatment with ouabain induces the development of a time-dependent hypertension (10,21,23,26,32,45,54) as well as regional changes in the ouabain-sensitive sodium pump activity and expression of the ␣-isoforms (45). This hypertension is also associated with a reduction of phenylephrine-induced contractile activity in the thoracic aorta, but not in caudal arteries, and with an increase in the negative endothelial modulation of the actions of phenylephrine in both arteries (45).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…As previously demonstrated, long-term treatment with ouabain induces the development of a time-dependent hypertension (10,21,23,26,32,45,54) as well as regional changes in the ouabain-sensitive sodium pump activity and expression of the ␣-isoforms (45). This hypertension is also associated with a reduction of phenylephrine-induced contractile activity in the thoracic aorta, but not in caudal arteries, and with an increase in the negative endothelial modulation of the actions of phenylephrine in both arteries (45).…”
Section: Discussionmentioning
confidence: 81%
“…nitric oxide; endothelial-dependent hyperpolarizing factor; phenylephrine THE PLASMA LEVELS of an endogenous circulating Na ϩ -K ϩ -ATPase inhibitor, characterized as ouabain or a closely related compound (17,36), are increased in several animal models of hypertension (19,39), as well as in human essential hypertension (20). Several studies have shown that chronic administration of ouabain induces hypertension, an effect that seems to be linked to the inhibition of the Na ϩ -K ϩ -ATPase (10,22,23,45,54), although sodium pump inhibition seems not to be the exclusive mechanism of the ouabain-hypertensive effect (26,31,32,52). This enzyme is found in most eukaryotic cells and is the main system involved in the maintenance of sodium homeostasis and the membrane potential, essential factors for controlling vascular tone and blood pressure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, neural and humoral mechanisms are closely linked. For instance, increased levels of brain ANG II, such as occurs in Dahl saltsensitive rats during high sodium intake, affect the tonic level of sympathetic activity as well as the magnitude of baroreflex-induced changes in sympathetic traffic (39,80). In humans with mild to moderate hypertension, the marked increase in plasma renin activity induced by a low-sodium diet has been shown to also be associated with a blunted baroreflex modulation of sympathetic neural drive (31).…”
Section: Physiological Changes In Baroreflex Functionmentioning
confidence: 99%
“…Além disso, apesar do efeito pressórico não requerer a glândula adrenal para sua ocorrência e não ser sensível a sal, observa-se o aumento das concentrações plasmáticas de aldosterona (MANUNTA et al, 1994). Também neste modelo de HA, a OUA ativa tanto mecanismos centrais quanto periféricos, que agem nos diferentes territórios cardiovasculares para produzir o aumento da pressão arterial CARGNELLI et al, 2000;DI FILIPPO et al, 2003;HUANG et al, 1994;HUANG, LEENEN, 1999; ROSSONI et al, 2002a e b;WENCESLAU et al, 2011;XAVIER et al, 2004a;ZHANG et al, 2009 (BRIONES et al, 2009;CARGNELLI et al, 2000; HERNANZ et al, 2008; KIMURA et al, 2000; ROSSONI et al, 2002a b;XAVIER et al, 2004a, b e c).Entre essas, verificou-se: a redução na resposta constritora à fenilefrina, observada em anéis de aorta torácica e artéria mesentérica superior; a não alteração nas respostas contráteis mediadas por agonistas α-adrenenérgicos nas artérias caudal, basilar encefálica, coronária e mesentérica de resistência (AMR); e, por outro lado, o aumento dessa resposta contrátil em anéis de artéria renal (BRIONES et al, 2009;CARGNELLI et al, 2000; HERNANZ et al, 2008; KIMURA et al, 2000; ROSSONI et al., 2002a b;XAVIER et al, 2004a GAYTON, 1990;HALL, 1986). Essas mudanças resultam no aumento da transferência de sódio e água do lúmen tubular para o capilar peritubular, contribuindo para o aumento na pressão arterial.…”
unclassified